Harders-klachte - Huygens, Constantijn 1596-1687 (1622)
In early January 1620, Maria van Mathenesse fell under the eyes of her fiancé, Jacob van Wassenaar, Lord of Warmond, near Leiden, through the ice and drowned. The English envoy Carleton describes this tragic event in a letter of 14 January 1620. On request from the same Carleton, Huygens writes, as mentioned to Daniel Heinsius, this sad four-part work Ter aóax vovvov (four tears). Huygens was inspired for this sad poem by the first idyll of Theocritus: 'Thirsis' lament for the death of Dafnis'. He probably knew Heinsius' edition of it. Perhaps that is the reason why Huygens is extra curious about Heinsius' opinion of these poems. The Haarlem priest Joan Albert Ban (1597–1644) composed emotive music for this poem.
Poems in Dutch, Latin, French and Italian version, all written in 1620
Bound in with 'Kerkuraia mastix', 'Batava Tempe' and 'Groete aen de ioffrouwen'
op den selven sin. In de welcke Thirsis vertoont dennHeere van Warmon, beclaghende het drouvich ongeval, sine Bruyd (wijlen dochter van den Heere van Matenes, Heere van Haserwoude) door Ys-braecke over-ghecomen
Keywords: 17th Century (1601-1700); Poetry; Lament; Netherlands